Efeitos de anestésicos gerais utilizados em cirurgias experimentais em ratos submetidos a testes preditivos de efeito ansiolítico e antidepressivo - Paula, Letícia Santos Herbst de (2017)
In experimental psychopharmacology, the behavioral evaluation is often preceded by stereotactic surgery to insert cannulas or electrodes in the central nervous system. During these surgeries, the rodents receive anesthetic and analgesic drugs to prevent unnecessary suffering. Previous studies showed that some general anesthetics, such as ketamine, induce acute and persistent antidepressant and anxiolytic-like effects. In this way, we evaluated whether other general anesthetics would also affect behaviors that would compromise the experimental data interpretation of other studies. Thus, we evaluate if tribromoethanol, chloral hydrate, thiopental and isoflurano would change behavior of animals submitted to the Forced Swimming Test (FST) and to the Elevated Plus-Maze (EPM). In a second experiment, we evaluate if an anesthetic dose of anesthetics that did not affect the analyzed behavior in the first experiment, could interfere with the detection of the antidepressant (imipramine) or anxiolytic (diazepam) effects in rats subjected to the TNF or LCE, respectively. Adult Wistar rats were intraperitoneally injected (single injection) with subanesthetic and anesthetic doses of chloral hydrate (50, 150 and 400 mg/kg); tribromoethanol (40, 90, and 250 mg/kg) or thiopental (05, 15 and 40 mg/kg). The control group received saline injections. Isoflurane was administered by inhalation in anesthetic dose (4% to induction and 2% for maintenance) or in subanesthetic doses (0,5, 1,5%), and the control group received air. The animals were tested in the FST 2 h and 7 days after injections. Independent groups of animals were tested in the EPM and in the open field (OF) 2 hours or 7 days after injection of the anesthetics. Tribromoethanol did not acutely (2h) or persistently (7 days) affect behaviors in the FST. Tribromoethanol (90mg/kg) increased exploration of the open arms in the EPM, indicating an acute anxiolytic-like effect. The anesthetic dose of tribromoethanol (250mg/kg) decreased the open arms exploration in the EPM 7 days after treatment, suggesting a delayed anxiogenic-like effect. A subanesthetic dose of chloral hydrate (150 mg/kg) reduced immobility time in the FST only acutely, suggesting an antidepressant-like effect. The anesthetic dose of chloral hydrate (400mg/kg) raised the exploration of the open arms in the EPM 2 h and 7 days after treatment, suggesting an acute and persistent anxiolytic-like effect. The anesthetic dose of thiopental (40mg/kg) acutely reduced immobility time and frequency in the FST, suggesting an antidepressant-like effect. Thiopental did not affect behaviors in the EPM. Isoflurano did not present any effect on behavior of TNF or EPM. The general anesthetics did not interfere in the detection of the antidepressant or anxiolytic effect of imipramine or diazepam, respectively. Our results showed that tribromoethanol and chloral hydrate are improper anesthetics in surgeries that precede behavioral tests related to anxiety, while isoflurane and thiopental proved to be suitable for use in this tests. The subanesthetic doses of tribromoethanol (90mg/kg) and chloral hydrate (150mg/kg) induce acute anxiolytic and antidepressant-like effects, respectively, while an anesthetic dose of thiopental induced acute antidepressant effect, suggesting that these drugs may be target of future studies for developing potential new medicine to treat anxiety and depression disorders.